STUDI KORELASI PENGGUNAAN VIDEO GAME DENGAN KESEHATAN PLAYER SAAT PANDEMI DI KOTA BATAM DENGAN PENDEKATAN MULTI-METODE - Jimmy Pratama; Novianto (UNIVERSITAS STEKOM, 2023)
In early 2020, the COVID-19 pandemic that swept across the world created disruption in life. COVID-19 is transmitted between people in proximity so physical (or social) distance is the main measure to reduce its spread. Lockdowns and quarantines due to the COVID-19 pandemic have led to an increase in video game players. The emergence of the trend of playing video games as one of the main ways of recreation has incited curiosity about the potential effects of playing video games on mental and physical health. The purpose of this study was to determine the correlation between video games and exercise on mental well-being during the COVID-19 pandemic in Batam city. The difference between this study and previous research is that there is yet any research that analyzes the correlation between the use of video games and exercise on health, especially mental well-being. The research used mixed quantitative and qualitative methods. The quantitative analysis used in this study was multiple regression analysis using the SPSS 26 program. The qualitative analysis was carried out by codification where the researcher categorizes answers from thematic analysis using NVivo (International QSR). Based on the results, it can be concluded that Exercise and Video Games have a positive correlation to Mental Well-Being. From the results of qualitative data, the researcher also identified a good impact from the use of Video Games towards Mental Well-Being.